RIFLESIONE DEI GIOVANI CATOLICI SULL’AMORE E IL SACRIFICIO DI GESU’ NELLA VIA CRUCIS - Abatan, Yofince; Abatan, Kasmirus (Pastoralia Jurnal Penelitian Dosen, 2025)
This research aims to explore the religious experiences of Young Catholich participating in the Stations of the Cross Service in various parishes on the island of Timor. This study uses a qualitative approach with a phenomenological design to explore the meaning, reflection of faith, and internalization of the values ​​of love and sacrifice experienced by participants. Data was collected through in-depth interviews, participant observation, and documentation. The results of the study indicate that the understanding and experience of young Catholic regarding the Stations of the Cross Service vary significantlyl Some participants were able to interpret the symbols and events of each station reflectively and relevant to their life experiences, meanwhile others participated in the service as a routine without deep understanding. These findings also indicate that the values ​​of love and sacrifice contemplated in the service are beginning to be integrated into daily life, although their application is not yet consistent. This research emphasizes the importance of contextual and participatory pastoral care so that the Stations of the Cross Service can be a means of faith formation for young people.